Desarrollo de la comprensión lectora a través de textos narrativos en estudiantes de la Unidad Educativa “Juan Francisco Yerovi” Cantón Alausí, periodo lectivo 2022 - Guerrero Alvear, Kerly Paulina (2023)
Low reading comprehension is a constant problem that teachers must face, representing an obstacle for the learning process. The present investigation of qualitative approach has the purpose of analyzing methods that contribute to the development of reading through narrative texts, this analysis includes the diagnosis of the comprehension level with the purpose of recognizing the deficiencies in the process, specifically in its literal, inferential, and critical dimension. For this purpose, the diagnosis has been made through a reading test, applied to thirty-six students of the Unidad Educativa "Juan Francisco Yerovi", Alausí Canton, students of the 2022 school year. Yielding information that shows failures in the interpretation of the text read, specifically in the inferential and critical comprehension, observing during the application of the exercise the lack of concentration and confidence of the sample, regarding the answers given during the practice. The proposal is based on the low results of inferential and critical comprehension and the strategy is developed within a cycle of workshops with narrative readings, in the subgenres of fable and story of classic works, with the purpose of giving the student the opportunity to raise ethical questions, encouraging their imagination and allowing the teacher to be creative in the practices. The design of the plan of practices aimed at consolidating reading comprehension through narrative texts will provide tools that could be applied within the subject of Language and Literature and could be adapted to any level of reader's study.